The Dangerous Dichotomy: Abandoning the ‘Proscriptive’ and ‘Prescriptive’ Classification of Fiduciary Duties and the ‘Proscriptive Limitation’ - Nicholas Saady (Bond Law Review)
The ‘proscriptive’ (negative) and ‘prescriptive’ (positive) dichotomy of fiduciary duties has attracted great contemporary interest, as the High Court has held that fiduciary duties are only proscriptive. The ‘dichotomy’ and ‘proscriptive limitation’ have been debated by scholars and judges. This article provides some perspective to the debate. It suggests that the proscriptive limitation is misleading because fiduciary duties are dynamic and unfixed, and because some fiduciary duties are positive. It also suggests that classifying duties within the dichotomy is unnecessary, overly complex, and potentially productive of error because it detracts from the proper focus of the fiduciary inquiry.